REVIEW ON METER DATA ACQUISITION SYSTEM - *, Sonia; Sharma, Dr. Neetu (IJRDO -Journal of Computer Science Engineering, 2017)
Reeling under an average AT & C losses of around 33%, it is quite impossible for power distribution sector to keep upthe desired economic pace without major reforms in the Power sector, especially in Distribution. System Integrator has beenworking closely in Power distribution sector to address AT & C loss reduction, bring transparency, improve customersatisfaction and increase employee productivity through right convergence of IT & Automation. Technology innovation canonly benefit the sector and system integration has major role to play in empowering the power distribution utilities. There is ahuge need for specialized, customized and upgraded system solution for the power sector and System Integration Powersolutions can help utilities to make a significant leap in Field Automation and reducing their Aggregate Technical andCommercial losses. The objective of Meter Data Acquisition Solution Provider is to collect meter data of DT and consumermeters at desired frequencies remotely and make available for DISCOM operations.Meter Data Acquisition project was initiated by WBSEDCL under power sector reforms in India called R-APDRP. Theobjective was to improve customer Service by providing accurate data for billing and also monitoring of energy consumed andoutages mainly at the downstream 11 KV Network level of the the Distribution Network. Another important objective wasestablishment of baseline data, billing, network analysis and energy accounting.Viola Systems delivered the solution as per specific demands of WBSEDCL to acquire data seamlessly from the existing 14,000meters which are installed at Substations, Distribution Transformers and Industrial consumer premises.